Integrated battery charger for electric vehicles based on a dual-inverter drive and a three-phase current rectifier - Fernao Pires, Vitor (2019)
This paper presents a new three-phase battery charger integrated with the propulsion system of an electric vehicle. The propulsion system consists of a dual-inverter topology connected to an induction motor via open windings. The electrical vehicles (EV) batteries are divided by two inverters. This will result in a drive with multilevel characteristics reducing the total harmonic distortion (THD) of the voltage applied to the motor. The modularity of the multilevel inverter will be maintained since two classical three-phase inverters are used. The charger will be fed by a three-phase high power factor current source rectifier. The motor windings will take the role of the DC-inductor required by the rectifier. In this way, an intermediate storage element between the grid and the batteries of the vehicle exist. For the control system of the battery charger, we propose the use of the instantaneous power theory and a sliding mode controller for the three-phase charger input currents. Finally, to verify the behavior and characteristics of the proposed integrated battery charger and control system, several tests are be presented.